The Self-Prioritization Effect: Self-referential processing in movement highlights modulation at multiple stages - Desebrock, C; Spence, C (Springer, 2021)
A wealth of recent research supports the validity of the Self-Prioritization Effect (SPE) – the performance advantage for responses to self- as compared with other-person associated stimuli in a shape-label matching task. However, inconsistent findings have been reported regarding the particular stage(s) of information processing that are influenced. In one account, self-prioritization modulates multiple stages of processing, whereas according to a competing account, self-prioritization is driven solely by a modulation in central-stage information processing. To decide between these two possibilities, the present study tested whether the self-advantage in arm-movements previously reported could reflect a response bias using visual feedback (Experiment 1), or approach motivation processes (Experiments 1 and 2). In Experiment 1, visual-feedback was occluded in a ballistic movement-time variant of the matching task, while, in Experiment 2, task-responses were directed away from the stimuli and the participant’s body. The advantage for self in arm-movement responses emerged in both experiments. The findings indicate that the self-advantage in arm-movement responses does not depend on the use of visual feedback or on a self/stimuli-directed response. They further indicate that self-relevance can modulate movement responses (predominantly) using proprioceptive, kinaesthetic, and tactile information. These findings support the view that self-relevance modulates arm-movement responses, countering the suggestion that selfprioritization only influences central-stage processes, and consistent with a multiple-stage influence instead.